2017
DOI: 10.1002/ajim.22802
|View full text |Cite
|
Sign up to set email alerts
|

Injury, illness, and disability risk in American seafarers

Abstract: Additional research in this vital American workforce may be useful to confirm these findings forming a basis for preventive interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 12 publications
2
9
0
1
Order By: Relevance
“…Our findings agree with previous research, regardless of differences in data sources comprising self-reported data,9 American telemedicine data8 and data on hospitalisation,6 of which all have demonstrated approximately an 1.6 times higher risk for injuries in non-officers than in officers. Higher injury rates in non-officers compared with officers can be accounted for mainly by the fact that non-officers’ work simply consists of more manual work, in which they are more exposed to injuries than officers whose work tasks primarily are non-manual.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings agree with previous research, regardless of differences in data sources comprising self-reported data,9 American telemedicine data8 and data on hospitalisation,6 of which all have demonstrated approximately an 1.6 times higher risk for injuries in non-officers than in officers. Higher injury rates in non-officers compared with officers can be accounted for mainly by the fact that non-officers’ work simply consists of more manual work, in which they are more exposed to injuries than officers whose work tasks primarily are non-manual.…”
Section: Discussionsupporting
confidence: 92%
“…We are not aware of any prior studies that have examined the association between age, occupation, nationality or any other determinants and specific types of injuries among seafarers. However, a previous study from the USA, although not addressing specifically these associations, demonstrated a distribution of seafarer injuries by injured body part8 which is quite similar to the distribution of injuries in the present study: the proportions of the combined category of upper and lower limb injuries, for instance, in our and the American study were 54% and 60%, respectively.…”
Section: Discussionsupporting
confidence: 86%
“…There is an insufficient amount of studies regarding the effects of length of seafarers' stay on board with medical repatriation. Based on the study done previously [7], there also have not been other studies regarding causes of seafarer repatriations from the Philippines. This is important to have an insight on appropriate health interventions depending on the length of stay of seafarers, an understudied economic body of great importance.…”
Section: Discussionmentioning
confidence: 99%
“…Residing far from land inside the vessel, seafarers are susceptible to occupational hazards and emergency medical condition with limited access to medical care and treatment options. Therefore, screening protocol implementation from clinics which offer pre-employment and occupa-tional health interventions are enforced among seafarers to avoid medical repatriation while they are on board [7].…”
mentioning
confidence: 99%
“…We assessed each selected study on 8 items and assigned up to a maximum of 9 points in 3 areas, including selection, comparability, and outcomes of interest with detailed analysis. As a result, we evaluated the quality of the selected studies based on agreed category scores ranging from 0 to 9: low quality (0-4), moderate quality (5)(6), and high quality (7)(8)(9). The assessment of the title and abstracts was performed by two (G.G.S.…”
Section: Quality Assessmentmentioning
confidence: 99%